Optimum design of reliable IC power networks having general graph topologies - Chowdhury, S. (26th ACM/IEEE Design Automation Conference, 1989)
This paper deals with the problem of sizing integrated-circuit power and ground distribution systems external to the logic modules constituting an integrated circuit. Several constraints associated with the reliability of the power and ground distribution systems are formulated. Algorithms are developed to determine the widths of the power and ground routes so that the area required by the routes is minimized subject to the constraints imposed. Run time results are included.